2009
DOI: 10.1021/jp8097928
|View full text |Cite
|
Sign up to set email alerts
|

Exchanges of Uranium(VI) Species in Amidoxime-Functionalized Sorbents

Abstract: Amidoxime (AO)-functionalized polymer sorbents used in this study were prepared by two different routes involving UV grafting and electron-beam grafting of acrylonitrile (AN) into poly(propylene) fibrous and microporous sheets, and subsequent conversion of AN to AO groups by reacting the precursor sorbent with hydroxylamine. The values of self-diffusion coefficient (D(s)) of UO(2)(2+) in fibrous and sheet AO sorbents were found to be 1.1 x 10(-6) and 2.3 x 10(-10) cm(2) s(-1), respectively. The higher diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 41 publications
2
91
1
Order By: Relevance
“…The related thermodynamic parameters calculated from the temperature-dependent isotherms are listed in Table 4. The positive values of standard enthalpy changes (∆H 0 ) indicated an endothermic process for the adsorption of UO 2 2+ on 2.0PAO/rGO composite that was consistent with our observed results and the literature [15,16,36]. The negative values of Gibbs free energy change (∆G 0 ) indicated that UO 2 2+ adsorption on 2.0PAO/ rGO was a spontaneous process [37].…”
Section: +supporting
confidence: 91%
See 2 more Smart Citations
“…The related thermodynamic parameters calculated from the temperature-dependent isotherms are listed in Table 4. The positive values of standard enthalpy changes (∆H 0 ) indicated an endothermic process for the adsorption of UO 2 2+ on 2.0PAO/rGO composite that was consistent with our observed results and the literature [15,16,36]. The negative values of Gibbs free energy change (∆G 0 ) indicated that UO 2 2+ adsorption on 2.0PAO/ rGO was a spontaneous process [37].…”
Section: +supporting
confidence: 91%
“…However, compared to the I D /I G value of rGO (~1.42), the I D /I G values of PAO/rGO composites were decreased to 1.04-1. 16, which suggests that the formed PAO on PAO/rGO composite surfaces mainly existed in the form of amorphous carbon materials. We have previously found that the modification of multiwalled carbon nanotubes (MWCNTs) with special functional groups, such as poly(aniline) [22], poly(methylmethacrylate) [23], and β-cyclodextrin [24], increased the disorder degree of MWCNTs.…”
Section: Adsorbent Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…Owens et al (2011) -4 , considered to likely be the rate limiting step (Das et al, 2008(Das et al, , 2009. Kinetic analysis of the model displacement reaction confirmed that the rate-determining step in the extraction process, was both the the complexing of uranyl by amidoxime group coupled with the dissociation of the carbonate group from the uranyl tricarbonate complex…”
Section: Seawater Uranium Adsorptionmentioning
confidence: 92%
“…A variety of adsorbents have been evaluated, hydrous titanium oxide, as one of the most widely described inorganic material (Yamashita et al, 1980b;, was found that carbonate ion from the uranyl tricarbonate complex (UO 2 (CO 3 ) 3 4− ) was released into the solution during the adsorption process (Yamashita et al, 1980a). Recently, synthetic polymers with amidoxime functional groups had been mainly used because of their high affinity in chelating U(VI) in seawater (Zhang et al, 2003;Das et al, 2009;Kim et al, 2014;Lashley et al, 2016). The uranium adsorption proceeded by ligand exchange of three carbonate ions on the central uranyl ion with two amidoxime groups, accompanied by deprotonations (Hirotsu et al, 1986).…”
Section: Introductionmentioning
confidence: 99%